The Mayo Clinic Arizona Spasmodic Dysphonia Experience: 24 Years and 686 Patients. (23rd August 2013) - Pollei, Taylor R.; Bansberg, Stephen F.; Adler, Charles; Lott, David G.; Patel, Alpen B.
Abstract : Objectives: 1) Outline onabotulinumtoxinA (onaBTX‐A) injection dose and frequency trends in adductor spasmodic dysphonia (AdSD) patients. 2) Assess correlations between onaBTX‐A injection dose, duration of breathiness, time to therapeutic onset, percent maximal benefit obtained, and duration of benefit. Methods: Retrospective chart review. Setting: Tertiary academic care center. Subjects and Methods: 686 patients with spasmodic dysphonia (SD) were treated with 6345 BTX injections between 1989 and 2013. This included 630 AdSD and 56 AbSD patients further subdivided into subgroups based on presence of vocal tremor (VT) and injection laterality. Injection frequency, dosing, laterality, and background demographic data were recorded in addition to subjective onaBTX‐A injection responses. Results: AdSD patients' symptom onset and injections began at an older age than AbSD patients (52.5; 60.6 years vs. 43.7; 50.0 years respectively; P = 0.0008) and had VT more frequently ( P = 0.0012). For the 380 AdSD patients (+/‐ VT) receiving over six injections, the average total onaBTX‐A dose was 5.0 units, which remained stable up to 15 years (year 15 dose mean= 5.29, std dev= 5.07). Using Pearson's correlation coefficients, there was no significant positive or negative correlation between onaBTX‐A dose and percent maximal benefit (p=0.760), duration of breathiness ( P = 0.618), dysphagia duration ( P = 0.142), benefit duration ( P = 3622), or time to therapeutic onset ( P = 0.618). Conclusions: Spasmodic dysphonia is effectively treated according to patient subjective response; however, more refined longitudinal analysis is needed to show if any objective correlation between injection dose and outcomes are present. Treatment methods and outcomes as described should aid others in developing best practice patterns.